Iowa Birdline update, January 3, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for January 3, 1994. Highlights include results from the Yellow River Forest Christmas count. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed